Illuminating the immunological landscape: mitochondrial gene defects in pancreatic cancer through a multiomics lens - Chi, Hao; Su, Lanqian; Yan, Yalan; Gu, Xiang; Su, Ke; Li, Han; Yu, Lili; Liu, Jie; Wang, Jue; Wu, Qibiao; Yang, Guanhu (Frontiers in Immunology, 2024)
This comprehensive review delves into the complex interplay between mitochondrial gene defects and pancreatic cancer pathogenesis through a multiomics approach. By amalgamating data from genomic, transcriptomic, proteomic, and metabolomic studies, we dissected the mechanisms by which mitochondrial genetic variations dictate cancer progression. Emphasis has been placed on the roles of these genes in altering cellular metabolic processes, signal transduction pathways, and immune system interactions. We further explored how these findings could refine therapeutic interventions, with a particular focus on precision medicine applications. This analysis not only fills pivotal knowledge gaps about mitochondrial anomalies in pancreatic cancer but also paves the way for future investigations into personalized therapy options. This finding underscores the crucial nexus between mitochondrial genetics and oncological immunology, opening new avenues for targeted cancer treatment strategies.